Registration of ‘NAROSORG2’ Sorghum Variety with Desirable Farmer Attributes for Uganda - Andiku, Charles; Lubadde, Geofrey; Aru, Charles John; Emanio, John; Adrogu Ugen, Michael; Ebiyau, Johnie (International Journal of Applied Agricultural Sciences, 2020)
Sorghum [Sorghum bicolor (L.) Moench] is the major cereal in Uganda that has recently evolved from being a food crop to a cash crop. However, low farm yields of less than 500 kg ha-1 have been recorded due to both abiotic and biotic stresses. Consequently, NaSARRI developed NAROSORG2, released in 2017, that can withstand some of the abiotic and biotic stresses. NAROSORG2 is a derived red seeded local landrace selection (IS8193) from East Africa, advanced by the International Crops Research Institute for the Semi-Arid Tropics (ICRISAT) through repeated bulk selections for tolerance against abiotic and biotic stresses. The agronomic evaluation was carried out in Uganda for the first and second rainy seasons of 2017 and the findings indicated that NAROSORG2, out-performed the check commercial variety, SESO3 with mean grain yield of 2740 kg ha-1 across the entire environment. It also recorded early days to 50% flowering of 65.23 days (early maturity variety) like the commercial check variety, SESO3 with a medium height of 165.35 cm. NAROSORG2 has superior agronomic traits of stay-green trait, resistant to bird damage due to high levels of tannins, drought, midge, and Striga tolerant, good for food, and local brew. Therefore, it will supplement other released varieties in contributing to food security and poverty alleviation among the rural communities in Uganda.
Keywords: Variety Registration; NAROSORG2; Evaluation and Genotypes